Assessing the efficiency of local government in Malaysia - Ismail, Suhaiza; Mohd Said, Julia; Mohd. Amin, Husniyati (Institut Perakaunan Negara, 2020)
The objective of this paper is to assess the level of efficiency of local government in Malaysia. Using data envelopment analysis (DEA), the research provides evidence on the efficiency of Malaysian local governments in terms of technical (TE), pure (PTE) and scale efficiency (SE). Secondary data obtained from financial statements of 35 local governments over a period of seven years are used. DEA is performed using three inputs (tax revenues, fees and charges, subsidies from central government) and four outputs (net book value of land and buildings, net book value of motor vehicles, net book value of equipment and fittings, cost of goods and services). The results show that most Malaysian local governments recorded high technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) with above 0.90 means scores.